PEGylation strategy to the development of analytical and therapeutic proteins - Santos, João Henrique Picado Madalena (2019)
Protein PEGylation is the covalent bonding of polyethylene glycol (PEG) polymers to amino acid residues of the protein and it is one of the most promising techniques for improving the therapeutic effect of biopharmaceuticals and long-term stability of protein-based biosensors. This chemical modification brings advantages to biopharmaceuticals, such as an increased half-life, enhanced stability, and reduced immunogenicity. Moreover, in the analytical field, PEGylation improves the multiple properties of protein-based biosensors including biocompatibility, thermal and long-term stability, and solubility in organic solvents. However, the use of PEGylated conjugates in the analytical and therapeutic fields has not been widely explored. The limited industrial application of PEGylated bioconjugates can be attributed to the fact that the reaction and separation steps are currently a challenge. The correct selection of the PEGylation reaction design and the purification process are important challenges in the field of bioconjugation. In this sense, the design and optimization of site-specific PEGylation reactions and application of aqueous biphasic systems (ABS) as purification platforms for PEGylated conjugates are the two main objectives of this thesis. Regarding the purification step, the efficient fractionation (i) of the PEGylated conjugates from the native protein and (ii) of the PEGylated conjugates based on their degree of PEGylation was studied. Centrifugal partition chromatography (CPC) was applied as a continuous regime platform based on ABS technology to efficiently purify the PEGylated proteins. The two proteins under study are L-asparaginase, an important biopharmaceutical applied in the treatment of acute lymphoblastic leukemia and cytochrome c, a promising biosensor. The current work developed in this thesis demonstrates the great potential of ABS in the fractionation of PEGylated proteins, under batch and continuous regime. In addition, in situ recovery of the PEGylated products through one-pot bioconjugation and ABS purification was successfully demonstrated for both enzymes studied. Although further research on scale-up is still required, the results presented show the relevance of ABS platforms for the development of separation processes of PEGylated proteins.